(untitled) (Jagannath University Journal of Life and Earth Sciences, 2025)
Climate change and anthropogenic activities has altered the land along the central coast of Bangladesh. It is already documented that this region faced different climate induced hazards and disasters due to lack of natural protections such as mangroves. Besides soil erosions are prominent in this region causes loss of ecosystem capacity to provide service. This study aims to assess the ecosystem integrity depletion and the impact severity of changing land in the ecological context over two decades (2000-2024). Using the Landsat imagery in Google Earth Engine (GEE) platform this study assessed the Land Use and Land Cover (LULC) for the year 2000 and 2024 and calculated the changes of land categories. Spatial severity of impact (SSI) is calculated from these changing land categories and the ecosystem integrity (EI) is also calculated for two years to assess the depletion of ecosystem from the base year 2000. The study found that the highest reduction has been observed in crop land, accounting for 69.4% to 52.5% of total area. The increasing number of homestead vegetation with rural settlement from 964.1 to 1602.9 sq.km reflects the increasing anthropogenic stress of the study area while waterbodies has been almost doubled from 2000 to 2024 indicating intensified erosion. Furthermore, the highest 58.5% of total areas facing moderate level of severity impact due to the negative alterations of land while eight unions across three districts had most of the areas (over 70%) facing very high impact of negative land alterations and most of these regions are on the edge of the Meghna estuary. On the other hand, the assessment of ecosystem integrity has shown that it reduced from 30963.6 to 29990.5 sq.km reflection of lowering ability of the land is mainly due to the degradation of land. The study also identified that almost 47.3% of total land is facing high depletion of ecosystem where 24.3% of total land have experienced very high degradation from the base year along the Meghna River estuary and the north eastern part of the study area. The improvement of the ecosystem also seen in most of the islands and in the central part of the study area. Among all other unions Hajipur union’s 98.57% of total areas experienced higher degradation. The Kala paraupazila have highest six number of unions have more than 70% areas high ecological degradation. The results of this research are pertinent in explaining the spatial configuration of ecological vulnerability in the extremely dynamic coastal setting will help policymakers and environmental managers to implement sustainable coastal land-use strategies, mitigating adverse ecological impacts and promoting resilience. Jagannath University Journal of Life and Earth Sciences, 10 (2): 211-238 (December 2024)